Needs Analysis in English for Specific Purposes (ESP) for Nursing Students - Yuriatson Jubhari; Rosmiaty; Nurliah (CV. Eureka Murakabi Abadi, 2022)
One indication of the cause, among others, is not optimal learning planning where the material provided is often not in accordance with the field of science taught by nursing students. Needs analysis is considered to be the cornerstone of English for Specific Purposes (ESP). The concept of Needs analysis has been different along the decades. Nowadays, the tasks of needs analysis is much more complex: it aims at collecting information about the learners and at defining the target situation and environment of studying ESP. This study was conducted in Politeknik Sandi Karsa. The number of students was 36 nursing students. The material offered by the researcher is 16 topics, all of which are responded very positively with the same high rank by all categories of respondents for inclusion as learning material. The results of this study are also expected to be used as a reference material for further research, namely syllabus/RPS planning and development of English teaching materials for nursing students. As conclusion that several important points that can be applied as well as an important reference in compiling English learning materials of Sub-skills in the field of speaking, listening, reading and writing which are ranked the first for each sub skill are: reading; read drawings/work schedules and understand the text, work contract in English at Politeknik Sandi Karsa Makassar Indonesia.